A Power Customer Data Relational Algorithm Based on Magnanimity Fuzzy Address Matching - Jin, Peng; Yang, Jing; Wang, Zongwei; Bu, Xiaoyang; Wu, Peng (Frontiers in Energy Research, 2021)
According to the short text and unstructured characteristics of customer address, a data association fusion method for address is proposed. In this method, the address is mapped to digital fingerprint by improved simhash technology, which effectively reduces the dimension of massive address and simplifies the similarity matching process of multi-source heterogeneous address. Furthermore, the weight setting of the eigenvector of simhash algorithm is improved by introducing special weight gain. Two-level index mechanism is established by the characteristics of address division and data structure of digital fingerprints, the time consuming of digital fingerprint comparison is greatly reduced. The experimental results show that calculation efficiency is greatly optimized, accuracy and coverage of the comparison is ensured. Through address matching among different databases, information fusion can be completed and the goal of connecting power customers' demands to power grid equipment is achieved.